(untitled) (Research, Society and Development, 2022)
Objectives: To identify the changes made, as a result of the Covid-19 pandemic, and their consequences in the respiratory physiotherapeutic treatment of patients with Cystic Fibrosis in the state of Piauí. Methodology: This is a cross-sectional, descriptive and quantitative research. The sample included all patients with a confirmed diagnosis of cystic fibrosis undergoing respiratory physiotherapeutic treatment in the state of Piauí, who were contacted and accepted to be part of the research. The collected data were tabulated and analyzed in Excel. Results: 70% of the sample said they felt unmotivated about the physical therapy treatment due to isolation. Home treatment was another challenge, as they found it difficult to perform breathing exercises and conducts. None of them had online physical therapy follow-up. The presence of some exacerbations of the respiratory clinical picture during the pandemic was also identified. Conclusions: It is concluded that the Covid-19 pandemic had a negative impact on the respiratory physiotherapeutic treatment routine of the individuals in the sample, leading to relevant changes in mandatory treatment, home care and quality of life.